IMPLEMENTASI METODE TSUKAMOTO UNTUK SISTEM PEMILIHAN MAKANAN SEHAT BAGI IBU HAMIL - Dhina Puspasari Wijaya; Doni Harisandi; Andri Pramuntadi; Deden Hardan Gutama (Universitas Alma Ata, 2023)
Healthy Food Selection System for Pregnant Women Is a web-based system designed to help pregnant women choose healthy foods during pregnancy (Trimester 1-Trimester 3) based on the number of calories needed in one day by taking into account the nutritional adequacy rate table. The food selection system is designed with ` =the Tsukamoto fuzzy logic method with the hope that the system can produce food recommendations based on the number of calories close to the ideal standard of the Nutritional Adequacy Ratio (RDA). In order To determine the level of accuracy of the system that has been made, validation of the ideal data on the Nutrition Adequacy Rate (RDA) is carried out with a total of 20 pregnant women. The results of the validation of the data generated by the system with ideal data obtained very close results with the largest error rate of 24.89%, so the conclusion is that the healthy food selection system by applying the Tsukamoto fuzzy logic method can be used to recommend healthy foods for pregnant women.